Evaluation of the behavior of cocoa pod husk flour in the elaboration of two food products - González Arias, Luisa Fernanda
The husk of the cocoa pod (Theobroma cacao) corresponds to the main residue of the industrialization of this fruit, and represents approximately 65% and 80% by weight, and is the main by-product of the process. Said shells are arranged by farmers in the cultivation, without any type of subsequent treatment, which during their degradation cause not only an environmental impact given the high volumes, but also favor the growth of microorganisms and pests, even of affectation. in cultivation. It is intended to develop this applied research project, with the aim of taking advantage of this raw material, which contains compounds of interest, for the elaboration of two products with food application from the flour obtained from the shells. Subsequently,evaluate the physicochemical and microbiological characteristics of the flour and, additionally, carry out a sensory analysis of the products obtained. The foregoing, in order to improve the living conditions of the cocoa farmers of the region, providing alternatives that favor the sustainability of the sector.